Analysis and evaluation of fruit traits of 106 white-flesh loquat germplasm resources - CHEN Xiuping; JIANG Jimou; DENG Chaojun; XU Qizhi; SU Wenbing (Guoshu xuebao)
[Objective] The study aimed to provide basis for efficient exploration and utilization of excellent white-flesh loquat [Eriobotrya japonica (Thunb.) Lindl.] resources as well as parent selection for breeding new variety through the investigation of diversity and correlation of main fruit traits of white-flesh loquat germplasm resources. [Methods] 106 white-flesh loquat resources conserved in the National Longan and Loquat Germplasm Resources Nursery (Fuzhou) were used, and ten fruit traits were measured, then coefficient of variation, correlation analysis and principal component analysis were performed among these traits. [Results] The coefficient of variation of fruit traits ranged from 9.3% to 34.9% among the investigated white-flesh loquat resources, and the diversity index of these traits ranged from 2.64 to 2.95. The fruit weight ranged from 6.9 g to 64.6 g, the average was 34.7 g and the coefficient variation was 34.9%; the fruit longitudinal diameter ranged from 2.12 cm to 5.95 cm, the average was 4.08 cm and the coefficient variation was 17.1%; the fruit transverse diameter ranged from 2.11 cm to 4.68 cm, the average was 3.77 cm and the coefficient variation was 13.4%; the fruit shape index ranged from 0.86 to 1.38, the average was 1.08 and the coefficient variation was 9.3%; the fruit lateral diameter ranged from 2.07 cm to 4.60 cm, the average was 3.55 cm, and the coefficient variation was 13.8%; the number of seeds per fruit ranged from 1.74 to 6.60, and the average was 3.31, and the coefficient variation was 24.4%; the weight of seed ranged from 0.78 g to 3.26 g, and the average was 2.07 g, and the coefficient variation was 23.7%; the flesh thickness ranged from 3.65 cm to 11.95 cm, the average was 7.87 cm, and the coefficient variation was 18.9%; The soluble solid content ranged from 9.4% to 17.4%, the average was 12.5% and the coefficient variation was 14.1%, the edible rate ranged from 41.5% to 76.5%, the average was 67.0% and the coefficient variation was 9.9%. There was no significant difference in seed number among white-flesh resources of different origin. Moreover, no significant differences in fruit weight, flesh thickness, soluble solids content and edible rate among white-flesh resources from Fujian, Jiangsu, Zhejiang and Guangdong provinces. However, Fujian was the main origin of white-flesh loquat with large fruit and high quality. While Yunnan, Sichuan and Guizhou had few white-flesh loquat resources with small size fruit with thin flesh and low edible rate. The correlation analysis showed that fruit weight was positively correlated with the fruit longitudinal diameter (r=0.90), fruit transverse diameter (r=0.95), fruit lateral diameter (r=0.91), fruit flesh thickness (r=0.79), seed number (r=0.58), and seed weight (r=0.63); the content of soluble solids was negatively correlated with the fruit weight (r=-0.46), fruit longitudinal diameter (r=-0.45), fruit transverse diameter (r=-0.49), fruit lateral diameter (r=-0.41), thickness of flesh (r=-0.55) and edible rate (r=-0.56); the edible rate was positively correlated with the fruit weight (r=0.69), fruit longitudinal diameter (r=0.75), fruit transverse diameter (r=0.74), fruit lateral diameter (r=0.69), fruit shape index (r=0.34), weight of seed (r=0.37), and fruit flesh thickness (r=0.80). The principal component analysis (PCA) showed that the contribution rate of the first principal component factor was 60.9%, reflecting the impotance of the fruit size. Twenty-five excellent resources were identified, among these: three accessions with fruit weight higher than 60.0 g, nine accessions with soluble solid content higher than 15.0%, three accessions with edible rate higher than 75.0%, two accessions with less than 2.0 seeds. More excitingly, eight of them showed advantages on fruit weight (≥40.0 g), soluble solid content (≥12.0%) and edible rate (≥68.0%) at the same time compared with the other white-flesh accessions. [Conclusion] The fruit traits of the white-flesh loquat resources were abundant, and twenty-five excellent resources of different types of white-flesh were screened out. This study would provide a basis for the exploration and utilization of the white-flesh loquat resources and the parent selection for loquat improvement in the future.